Gymnotus refugio, a new and endangered species of electric fish of the Gymnotus pantherinus species-group from southern Brazil (Gymnotiformes: Gymnotidae) - Giora, Julia; Malabarba, Luiz Roberto (Zootaxa, 2016)
Gymnotus refugio, new species, is described from coastal rivers of Rio Grande do Sul and Santa Catarina states, Brazil. It is diagnosed from most species of the Gymnotus pantherinus species-group by the coloration pattern, further differing from G. pantherinus and G. capitimaculatus on the basis of morphometric and meristic characters. The new species represents the most meridional record of the G. pantherinus species-group.